Does Low Skilled Immigration Cause Human Capital Polarization? Evidence from Italian Provinces - Giorgio Brunello; Elisabetta Lodigiani; Lorenzo Rocco (Institute of Labor Economics (IZA), 2017)
While there is a vast literature considering the labour market effects of immigration, less has been done to investigate how immigration affects the educational choices of young natives. Using Italian provincial data and an instrumental variables strategy, we show that the recent increase in the immigration of low skilled labour has produced human capital polarization, i.e. the contemporaneous increase in the share of natives with less than high school and not enrolled in school and in the share with a college degree or enrolled in college. This evidence is stronger for males than for females. We adapt the standard Card's model of educational choice and spell out under what conditions human capital polarization occurs. We estimate wage equations by gender and find that these conditions are satisfied, especially for Italian males.
Keywords: J26; H55; J21; J14; J11; 330; low skilled; immigration; human capital; Italy